DINAMIKA PENYELESAIAN SENGKETA HUKUM KELUARGA ISLAM DI INDONESIA (Studi Komparasi di Thailand) - Sa'adah, Isqi Dzurriyyatus; Farhi, Eriz Rizqiyatul; Rosadi, Aden; Yuniarti, Sri (Universitas Nurul Jadid, 2024)
This journal aims to investigate the dynamics of dispute resolution in the realm of Islamic family law based on legislation in Indonesia as well as its comparison in the legal system in Thailand, focusing on the comparison between the two countries in revealing the differences in the legal frameworks used, practices and procedures for dispute resolution, as well as what are the real challenges in their implementation, then looking at which points are the similarities as well as the differences between these two Asian countries. The research utilizes qualitative analysis with a normative or doctrinal examination of legal norms, with the provisional hypothesis highlighting that Indonesia has a systematic and nationally applicable Islamic family law system, while Thailand only implements Islamic family law in four specific southern provinces. The findings also indicate that despite efforts to expand out-of-court enforcement of Islamic family law, challenges such as lack of clarity in the law and uncertainty of enforcement remain obstacles. Thus, this study suggests the need to improve the Islamic justice system to ensure the resolution of Islamic family disputesKeywords : Dipute Resolution, Indonesia, Islamic, Thailand. ABSTRAKJurnal ini hendak menginvestigasi dinamika penyelesaian sengketa dalam ranah hukum keluarga Islam berdasarkan perundang-undangan di Indonesia juga komprasinya dalam sistem hukum di Thailand, dengan fokus pada perbandingan antara kedua negara dalam mengungkap perbedaan kerangka hukum yang digunakan, praktik dan prosedur penyelesaian sengketa, serta apa yang menjadi realitas tantangan dalam implementasinya, selanjutnya melihat titik mana yang menjadi persamaan juga pembeda dua negara Asia ini. Penelitian menggunakan analisis kualitatif dengan pendalaman norma hukum (normatif atau doctrinal), dengan hipotesa sementara menyoroti bahwa Indonesia memiliki sistem hukum keluarga Islam yang sistematis dan berlaku secara nasional, sedangkan Thailand hanya menerapkan undang-undang keluarga Islam di empat provinsi selatan tertentu. Temuan juga mengindikasikan bahwa meskipun terdapat upaya untuk memperluas penegakan hukum keluarga Islam di luar pengadilan, tantangan seperti kurangnya klaritas dalam undang-undang dan ketidakpastian penegakan hukum tetap menjadi hambatan. Demikian penelitian ini menyarankan perlunya peningkatan sistem peradilan Islam guna memastikan penyelesaian sengketa keluarga Islam.Kata Kunci: Indonesia, Islam, Penyelesaian Sengketa, Thailand.